Seasonal patterns of drosophilid flies and parasitoid wasps attracted to rotting fruit and vegetable baits in Canterbury, New Zealand. Issue 1 (2nd January 2017) - Hodge, S.; Ward, D. F.; Merfield, C. N.; Liu, W. Y. Y.; Gunawardana, D.
ABSTRACT: Although Drosophilidae and associated hymenopterous parasitoids have been the subject of much field and laboratory ecology in many parts of the world, the system has been relatively neglected in New Zealand. This study investigated the seasonality of Drosophila, Scaptodrosophila and associated hymenopterous parasitoids in Canterbury by using traps baited with banana, orange, mushrooms, other fruits and vegetables and vinegar at two locations, New Brighton and Lincoln. From 176 sampling events, seven species of drosophilid were collected: Drosophila busckii ; D. funebris ; D. hydei ; D. immigrans ; D. pseudoobscura ; D. simulans ; and Scaptodrosophila enigma . Seven species of adult parasitoid wasps were also recorded in the traps: the braconids Dinotrema longworthi, Aphaereta aotea, Asobara tabida, Aspilota andyaustini ; the ichneumonid Campoplex sp.; and two encyrtids, including Tachinaephagus zealandicus . The more abundant drosophilid species were found throughout the year, with fewer species occurring in the winter months (June–August). Parasitoids tended to be found more often in the warmer months, with only one specimen (of Aspilota andyaustini ) collected between June and October. All seven species of drosophilids were obtained from traps with banana and mushroom baits. Mushroom proved valuable for obtaining parasitoids, with five species being recorded on this bait. Although the wasps were all captured along with adult Drosophila, it is believed only one species, Asobara tabida, is a confirmed drosophilid parasitoid. Further field study, on a wider geographic scale, in natural and modified habitats, is required to provide additional information on the phenology, biogeography and parasitoid–host interactions of drosophilids in New Zealand.